INTERCULTURAL COMMUNICATION AMONG STUDENTS AND YOUTH IN LABUHANBATU SELATAN DISTRICT - Siregar, Faizal Anwar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
The Indonesian nation is a nation whose society is heterogeneous, namely a society consisting of various ethnic groups, religions, languages, customs and others. Communicating to meet the needs of individual or group life, of course, interact with other ethnic groups as well as with other individuals or groups with different cultural backgrounds, so on that basis the emergence of intercultural communication. This study aims to find out how the escalation of life that contains elements of cultural diversity, in this case focused on students and youth in an organization, namely the South Labuhanbatu Youth and Student Movement (GEPMA LABUSEL). Such as verbal and nonverbal communication messages, obstacles, and problems such as (conflicts) that are encountered in intercultural communication among students and youth in South Labuhanbatu. In addition, this study uses a qualitative research approach, namely, by using data collection techniques, reference sources for journals, books, and other data, then through interviews, observations, and documentation. From the results of the study, it was found that the ethnic groups in the South Labuhanbatu area had differences in terms of appearance, lifestyle, customs, ways of interacting, language/dialect. The need to pay attention to and change the orientation of the interaction process in intercultural communication in various levels of society, especially in the scope of students and youth such as the organization above at this time, is due to attitudes or behaviors that cause conflicts that hinder the communication process in determining certain rights or goals and of course minimize the sense of belonging. community unity.